Treatment of anxiety-depressive disorders in patients with chronic pain - Sapon, Daria (Psychosomatic Medicine and General Practice, 2017)
Background. The problem of the treatment of anxiety-depressive disorders in chronic pain is not solved, considering the significant somatization of psychopathological manifestations in dorsalgia and fibromyalgia; triggering and aggravating role of stress; lack of clear clinical recommendations for the management of patients with combined disease states. Methods and materials. 164 patients with anxiety-depressive disorders and chronic pain were divided into the study group (n=81) with fibromyalgia and the comparison group (n=83) with joint pain (M25.5) or dorsalgia (M54 .0-9). Both groups were randomized into psychotherapeutic or pharmacotherapeutic treatment: F-Ph (fibromyalgia patients, psychopharmacotherapy - 42 persons), F-Ps (fibromyalgia patients, psychotherapy - 39 persons), JD-Ph (joint pain/dorsalgia patients, psychopharmacotherapy - 45 persons) JD-Ps (joint pain/dorsalgia patients, psychotherapy - 38 persons). Psychopharmatherapy included SSRIs, SNRIs, and pregabalin in standard dosages according to the instructions. Psychotherapeutic interventions involved the following methods: psychoeducation, progressive muscle relaxation, rational therapy, art therapy, elements of cognitive behavioral therapy. Evaluating the effectiveness of the treatment was carried out at week 4 and 12 with Hamilton anxiety and depression scales (HAM-A and HAM-D). Results. At week 4 of treatment, the most significant reduction in anxiety and depression symptoms occurred in psychopharmacotherapy groups, compared to psychotherapy. In particular, in patients with fibromyalgia (13.5 vs. 7.8, p=0.026 and 8.2 vs. 5.9, p=0.048, respectively). At week 12 (end of treatment), there wasn’t noted any significant difference between the effectiveness of pharmacotherapy and psychotherapy interventions for reducing anxiety and depression symptoms. Conclusion. These data indicate the similar effectiveness of pharmacotherapy and psychotherapy in the treatment of anxiety and depression symptoms in patients with chronic pain.